Historical researches of War crimes and genocide consequenses in Lithuania in 1992–2002 - Anušauskas, Arvydas (Genocidas ir rezistencija, 2002)
Historical and legal research has been very dynamic in the last decade since the adoption of the Law on Responsibility for the Genocide of the Lithuanian Population on 9 April 1992. There has been a shift from reading works on the history of Lithuanians in exile to large–scale research. The historical research can be divided into several phases, which are linked to the establishment of various institutions and emphasis on different aspects. There were several phases of research over ten years, each marked with its own institutional and political specificities.